2015
DOI: 10.1093/ndt/gfv084
|View full text |Cite
|
Sign up to set email alerts
|

High versus low dialysate sodium concentration in chronic haemodialysis patients: a systematic review of 23 studies

Abstract: There is currently no definite evidence proving the superiority of a low or high uniform DNa(+) on hard or surrogate endpoints in maintenance haemodialysis patients. Future trials adequately powered to evaluate the impact of different DNa(+) on mortality or other patient-centred outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 33 publications
0
41
1
Order By: Relevance
“…Although some observational studies have reported lower weight gains and lower blood pressure with lowering the dialysate sodium concentration, other studies only noted a minor effect, and others reported increased mortality associated with lower dialysate sodium . As such there has been debate as to the optimum choice of dialysate sodium …”
Section: Introductionmentioning
confidence: 99%
“…Although some observational studies have reported lower weight gains and lower blood pressure with lowering the dialysate sodium concentration, other studies only noted a minor effect, and others reported increased mortality associated with lower dialysate sodium . As such there has been debate as to the optimum choice of dialysate sodium …”
Section: Introductionmentioning
confidence: 99%
“…Studies for which sodium was the active ingredient were not considered in the review. Studies focusing on the electrolytic composition of dialysis solutions, a specific topic which has already been reviewed elsewhere [15], or enteral/parenteral nutrition were also excluded from the present review. The study designs of interest included: experimental studies (randomized controlled trials) and quasi-experimental studies (non-randomized controlled trials, controlled or non-controlled before-after studies and interrupted time series), observational studies (cross-sectional, retrospective/prospective cohort, or case-control studies).…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, patients treated with higher dialysate Na can tolerate the HD session better, but often at the price of higher IDWG and increased thirst and blood pressure levels [60, 61]. …”
Section: Management Of Fluid Overloadmentioning
confidence: 99%